Severe mental illness and diabetes mellitus Type 2 - De Hert, M.; Detraux, J.; Vancampfort, D.; Yu, W.; Correll, C.U. (Die Psychiatrie, 2012)
Three to four percent of the world’s population has diabetes mellitus (DM), which leads to a markedly increased risk of blindness, renal failure, amputation and cardiovascular disease, and reduces average life expectancy by 10 or more years. However, the prevalence of this severe metabolic disease among patients with severe mental illness (SMI), including schizophrenia, bipolar disorder, schizoaffective disorder and major depressive disorder, is higher than in the general population and its impact on these individuals significantly greater. We reviewed the literature on what is currently known about the relationship between SMI and DM and report prevalence rates of DM type 2 as well as important individual lifestyle choices and side effects of antipsychotic and antidepressant treatment, which each account for much of the increased risk of this metabolic disease in these patients. However, the exact cause and effect relationships between the prescription of these medications and DM type 2 still remain to be elucidated.
Keywords: Diabetes mellitus; severe mental illness